פתרו עבור x: y = sqrt ((4x + 1) / (3x-3))?

פתרו עבור x: y = sqrt ((4x + 1) / (3x-3))?
Anonim

תשובה:

# x = (1 + 3y ^ 2) / (3y ^ 2-4) # #

הסבר:

# "שים לב" sqrtaxxsqrta = (sqrta) ^ 2 = a #

# y = sqrt ((4x + 1) / (3x-3)) #

#color (כחול) "ריבוע משני הצדדים" #

# y = 2 = (sqrt ((4x + 1) / (3x-3)) ^ 2 #

# rArry ^ 2 = (4x + 1) / (3x-3) # #

# rRrry ^ 2 (3x-3) = 4x + 1larrcolor (כחול) "cross-multiplying" #

# rArr3xy ^ 2-3y ^ 2 = 4x + 1 #

# rArr3xy ^ 2-4x = 1 + 3y ^ 2 colorrcolor (כחול) "איסוף מונחים ב- x" #

#rArrx (3y ^ 2-4) = 1 + 3y ^ 2larrcolor (כחול) "גורם" #

# rRrxx = (1 + 3y ^ 2) / (3y ^ 2-4) (y! = + - 4/3) #

#color (כחול) "כצ'ק" #

# "תן x = 2" #

# "ולאחר מכן" y = sqrt (9/3) = sqrt3 #

# "תחליף את הביטוי עבור x אנחנו צריכים לקבל 2" #

# (= 1 + 3) / (9-4) = 10/5 = 2 #